The relation between foreign direct investment in growth and human development in Latin America, 1996-2019 - Varela, Marcelo (2023)
Latin America each year receive large flows of direct foreign investment; however, these money flows have not generated the expected macroeconomic effects, neither it has an impact on human development, which has determined a broad debate on the effectiveness of foreign direct investment. This study examines the effectiveness of foreign direct investment on economic growth and human development in Latin America during the period 1996-2019. To measure the relationship between foreign direct investment and economic growth, and its relationship with human development, two panel data econometric models are used. The first model measures the relationship of foreign direct investment with economic growth, and the second model measures the relationship of foreign direct investment with human development. The results under the premise that growth is not the same as development show that direct foreign investment contributes positively to economic growth, while the money flows sent abroad captured from the balance of net income in the balance of payments sent to the exterior affect negatively to human development